Aplikasi Deteksi Motif dan Crawling Produk Batik Banyuwangi Berbasis Web - Lutfi Hakim; Nurul Hidayati Novitasari; Sepyan Purnama Kristanto; Dianni Yusuf (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2022)
Batik is a high cultural heritage that is worldwide and made by the Indonesian nation. The motifs arranged in batik express the meaning of certain cultural values or moral lessons. Therefore, each region in Indonesia develops its own batik with patterns or motifs that are characteristic of their respective regions, Banyuwangi Regency is no exception. Until now, more than 30 batik motifs are spread and traded in Banyuwangi. However, with the growing potential of Banyuwangi batik, digital technology support is still not optimal. Therefore, in this study, an application was developed that can detect via web devices and also extract information related to Batik Banyuwangi products in the marketplace. Applications developed using the Python programming language with the Django framework and MySQL database. The detection process is run with the *h5 extension model using the tensorflow library as well as the selenium and beautiful soup libraries for crawling. The system development method uses the Extreme Programming method and the results of testing using Black box testing are 78.57% of the application features are declared valid and the rest need improvement. In addition, in addition to testing with black-box testing, testing for the implementation of web-crawling was also carried out and the results obtained 16.89% stated that there was a difference between the crawling results with the proposed technique and the actual amount of data. The results of this study are expected to be the beginning in developing the Banyuwangi Batik Gallery application.